Low Molecular Weight Heparin-Induced Skin Necrosis: A Case Report - Anastasios Katsourakis; George Noussios; George Kapoutsis; Efthimios Chatzitheoklitos (Case Reports in Medicine)
Low molecular weight heparins (LMWHs) are the standard agents used for antithrombotic therapy and prophylaxis. Despite their widespread use, reports about adverse effects from LMWHs are very scarce. Heparin-induced skin necrosis at the injection site is a rare adverse effect, more commonly associated with unfractionated heparin (UFH) rather than with LMWH, while its mechanism remains unclear. This paper deals with the enoxaparin induced skin necrosis.